The Development of Flipbooks Integrated With Malay Culture for English Department Students - Kumalasari, Cyintia; Marhamah, Marhamah; Wulandari, Fitri (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Writing is a complex skill in English subject, because it includes logical, structured ideas and needs proficiency. However, the ability of English Department students to understand how to write a good paragraph is still low. Besides, this study aims to implement the use of flipbooks to enhance the learning outcomes of the Paragraph Writing subject for English Department students. In general, this study aims to design -module use of flipbooks in enhancing their writing skills. The material used is about Malay culture to remind them about their place of origin. ADDIE model was used to enhance quality and effectiveness. The results of this research showed that the implementation of Flipbook teaching materials based on local wisdom is effective and successful in raising learning outcomes. According to the study's findings, each validator considered the e-module to be acceptable in terms of the media and content.